Solid modelling with constraints and parameterised features - Lafon, J.-C. (Proceedings. 1998 IEEE Conference on Information Visualization. An International Conference on Computer Visualization and Graphics (Cat. No.98TB100246), 1998)
This paper presents solutions to the interactive design of 3D objects with parameterised features and constraints. In the introduction, we describe some new industrial needs in computer-assisted design. In the second part, we give an outline of an object-oriented dual modeller we have developed. The third part is devoted to the parametric and constraint-based design approach. The subject of the last part is design by features and the evolution toward the functional design of complex 3D objects.